Sequential occurrence of acute hepatitis B among members of a high school Sumo wrestling club. Issue 10 (7th November 2013) - Bae, Sung Kwan; Yatsuhashi, Hiroshi; Takahara, Ikuko; Tamada, Yoko; Hashimoto, Satoru; Motoyoshi, Yasuhide; Ozawa, Eisuke; Nagaoka, Shinya; Yanagi, Kenji; Abiru, Seigo; Komori, Atsumasa; Ishibashi, Hiromi
<x xml:space="preserve">Abstract</x> A 17‐year‐old male was admitted to our hospital and diagnosed with acute hepatitis B. Six weeks later, a 15‐year‐old male was admitted with acute hepatitis B as well. They were Sumo wrestling players in the same club. A detailed survey in the club revealed that a 28‐year‐old male coach was a hepatitis B surface antigen carrier with high‐level viremia. The consistency of hepatitis B virus (HBV) DNA in the infected players was revealed by analyzing the complete HBV genome sequences. Sumo players are more likely to get injured, including cuts and bleeding, compared with players of other sports because of the characteristic wrestling style. Several past reports have suggested that highly viremic HBV carriers have high HBV DNA titers in both their blood and other body fluids such as sweat. In our cases, percutaneous HBV transmission through the bleeding wounds was the most probable infection route. We conclude that a universal HBV immunization program should be introduced urgently in Japan, similar to those implemented in other countries worldwide.